REALIZATION OF CLUSTER APPROACH AS DETERMINANT OF REGIONAL INNOVATIVE DEVELOPMENT - Pavel A. Krasnokutskiy (Вестник Донского государственного технического университета, 2018)
The realization of the cluster approach as one of the upcoming trends of the regional economy development is considered. The role of clusters in the innovative development of regions is specified. Perspectiveness of the cluster approach application in Russia is analyzed.